Session Topic: Tax Depreciation Reform: Discussion - Coen, Robert M.; David, Martin (Journal of Finance, 1972)
Robert M. Coen, Martin David, Session Topic: Tax Depreciation Reform: Discussion, The Journal of Finance, Vol. 27, No. 2, Papers and Proceedings of the Thirtieth Annual Meeting of the American Finance Association, New Orleans, Louisiana, December 27-29, 1971 (May, 1972), pp. 534-541